1969
DOI: 10.1128/aem.17.3.355-359.1969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vaccine, Route, and Schedule on Antibody Response of Rabbits to Pasteurella tularensis

Abstract: The response of the rabbit to viable or killed whole-cell Pasteurella tularensis vaccines was studied. The most practical preparation for the production of anti-P. tularensis antibodies was viable organisms of the live vaccine strain (LVS). The intravenous route of administration proved superior to either the subcutaneous or intradermal routes, and incorporation of LVS into Freund's adjuvants did not result in increased levels of antibody. Short-term hyperimmunization, three injections at weekly intervals, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Two studies evaluated aspects of LVS inoculation of the New Zealand white rabbit 71, 72 . Rabbits survived LVS inoculation given percutaneously or subcutaneously (10 5 organisms) and extended survival after SCHU S4 challenge by 3 days compared to nonvaccinated SCHU S4 challenged rabbits.…”
Section: Rabbit Modelsmentioning
confidence: 99%
“…Two studies evaluated aspects of LVS inoculation of the New Zealand white rabbit 71, 72 . Rabbits survived LVS inoculation given percutaneously or subcutaneously (10 5 organisms) and extended survival after SCHU S4 challenge by 3 days compared to nonvaccinated SCHU S4 challenged rabbits.…”
Section: Rabbit Modelsmentioning
confidence: 99%
“…F *A comparative study of antigens extracted from Pasteurella tularensis by various chemical procedures has not been reported. Viable and killed whole-cell vaccines usually have been employed for producing antisera in animals (2,4,6). A few studies on antigenic extracts have been reported, but the emphasis was on immunogenicity (5,7) or their utility as a serological reagent for assessing preformed antibody (1,2,6,12).…”
mentioning
confidence: 99%
“…Previous studies (4) demonstrated that shortterm hyperimmunization with P. tularensis LVS would increase the P. tularensis agglutinin titers of rabbits. This procedure was combined with that of sequential immunization used in the current studies.…”
Section: Resultsmentioning
confidence: 95%